Pengaruh pH pada Pembentukan Nano-powder TiO2 Fase Anatase dan Sifat Fotokatalisnya: Nur AS Ichzan, Vicran Zharvan, Rizqa Daniyati, Hadi Santoso, Gatut Yudoyono, Darminto - Nur Ichzan AS, Nur Ichzan AS; Vicran Zharvan, Vicran Zharvan; Rizqa Daniyati, Rizqa Daniyati; Hadi Santoso, Hadi Santoso; Gatut Yudoyono, Gatut Yudoyono; Darminto, Darminto (Jurnal Fisika dan Aplikasinya, 2025)
This paper describes the effect of different pH solution on the formulation of anatase TiO2 nano-powders to enhance photocatalytic activity. TiO2 powders were synthesis using co-precipitation method at different pH precursor solution which is 9, 11 dan 12. TiO2 nano-powders were analyzed using X-Ray Diffractometry (Philips X-pert) and UV-Vis Spectrophotometer (Genesis 10S). The Estimation of crystalline size would be analyzed by Rietveld method while the energy band gap was calculated by using Tauc method. Crystalline size are 11.80 nm, 14.96 nm and 15.87 nm respectively. Photocatalytic activity experiment used methylene blue solution with irradiation of UV lamp for 5 hours and measured every 1 hour. The highest absorption coefficient was 1,80 with wavelength 265 nm to pH 12. The results showed that the difference of pH on synthesis process inflQuenced on crystals size of TiO2 powders. The experimental results also showed the smaller crystals size of TiO2 powders, the more effective in degrading the concentration of methylene blue solution. The maximum efficiency of the materials provided is 55.44% at pH 9.